(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical, paraclinical characteristics and surgical outcomes of uterine fibroid myomectomy at the National Hospital of Obstetrics and Gynecology. Materials and methods: A prospective cross-sectional descriptive study was conducted on 244 patients diagnosed with uterine fibroids, indicated for and undergoing myomectomy at the National Hospital of Obstetrics and Gynecology from June 2025 to November 2025. Results: The mean age was 37.9 ± 5.8 years. Surgical approaches included open surgery (61.1%), laparoscopic surgery (29.9%), and hysteroscopic surgery (6.6%). Most patients had single fibroids (79.5%) with a mean largest diameter of 67.3 ± 24.1 mm; intramural and subserosal types accounted for 36.5% and 17.2%. Uterine size and tumor diameter ≥ 80 mm were risk factors for choosing open surgery (OR = 3.06; p < 0.05), while subserosal fibroids significantly reduced this likelihood (OR = 0.21; p < 0.001). The rates of uterine cavity entry (9.4%) and postoperative fever (8.6%) were higher in the open surgery group (p < 0.05). Blood transfusion rates were low (4.5% in total) and not significantly different between groups. The mean hospital stay was 4.1 ± 0.6 days. Conclusion: Fibroid location and size are the main factors influencing surgical approach selection. All surgical methods were safe with low complication rates.